Graph theoretic approach for analysis of power grid - Zhang, Zhuozhi (Nanyang Technological University, 2020)
The deregulation of electricity supply from producer to consumer has transformed the electricity distribution structure from an otherwise tightly coupled network to semi-loosely coupled distribution network. With many entities involved in the whole distribution network, it is imperative that a good understanding of the correlational inter-connectivity among all the entities will be useful for planning and management. Due to the increase in the amount of temporary renewable energy, it has become a new variable defining the electricity market mechanism. And the structure of part of the modern power value chain. Graph theoretic approach provides a way of modeling from an organizational perspective. Using the concept of structural balance, it can be envisaged that this approach will serve as a means for pre-emptive planning and risk management purpose.